MACROBENTHOS OF THE CRENAL AND RITHRAL ZONES OF A TYPICAL «SALMON» RIVER IN NORTHEASTERN SAKHALIN ISLAND (ON EXAMPLE OF THE DAGI RIVER) - V. S. Labay; A. I. Novoselova; O. N. Berezova; O. B. Sharlay; T. S. Shpilko; V. D. Nikitin; A. P. Prokhorov (Известия ТИНРО, 2019)
Structure and quantitative indices of macrobenthos, features of its distribution along the river bed, and basic communities of macrobenthos are described for the crenal and rithral zones of the Dagi River (northeastern Sakhalin) on the data collected in the expedition of Sakhalin State University in September 2017. Five river landscapes are described: 1) plain riverbed with significant alluvial forms; 2) mountain riverbed with significant alluvial forms; 3) plain riverbed with weak alluvial forms; 4) wellhead zone of a plain riverbed with significant alluvial forms; 5) estuary. The main elements of the river bed are partially mixed in the middle stream: the mountainous landscapes with significant alluvial forms are overlapped with the plain landscapes with weak alluvial forms. Distribution of macrobenthos along the river bed and the types of bottom communities are clearly corresponded with the river landscapes. So, the macrobenthos distribution in the Dagi River is physically controlled: the species diversity and abundance of macrozoobenthos increases downstream from the crenal to the rithral zone and further to the combined rithral-potamal zone. A significant increasing of the biomass is noted in the middle and lower rithral zone due to aggregations of freshwater pearl mollusc Margaritifera dahurica which confine with the spawning grounds of pacific salmons. The most common are the bottom communities of Hexatoma and Gammarus lacustris, which are noted almost in all surveyed areas. Other bottom communities are landscape-specific. In the rithral zone, composition and structure of macrobenthos are determined by distance to the riverbank, type of bottom sediments, flow velocity, and lithodynamic regime, so the communities form a consequence determined mainly by lithodynamic regime — the Hexatoma community in the lithodynamic zone of transportation could be followed either by the communities of Trichoptera, Plecoptera, and Diptera in the lithodynamic zone of erosion or by the communities of amphipods G. lacustris and larvae of day-flies Ephemera sachalinenesis in the lithodynamic zone of accumulation.